A dialysis medium refreshment cell culture set‐up for an osteoblast‐osteoclast coculture. Issue 4 (6th January 2023) - Vis, Michelle Anna Maria; de Wildt, Bregje Wilhelmina Maria; Ito, Keita; Hofmann, Sandra
Abstract: Culture medium exchange leads to loss of valuable auto‐ and paracrine factors produced by the cells. However, frequent renewal of culture medium is necessary for nutrient supply and to prevent waste product accumulation. Thus it remains the gold standard in cell culture applications. The use of dialysis as a medium refreshment method could provide a solution as low molecular weight molecules such as nutrients and waste products could easily be exchanged, while high molecular weight components such as growth factors, used in cell interactions, could be maintained in the cell culture compartment. This study investigates a dialysis culture approach for an in vitro bone remodeling model. In this model, both the differentiation of human mesenchymal stromal cells (MSCs) into osteoblasts and monocytes (MCs) into osteoclasts is studied. A custom‐made simple dialysis culture system with a commercially available cellulose dialysis insert was developed. The data reported here revealed increased osteoblastic and osteoclastic activity in the dialysis groups compared to the standard nondialysis groups, mainly shown by significantly higher alkaline phosphatase (ALP) and tartrate‐resistant acid phosphatase (TRAP) activity, respectively. This simple culture system has the potential to create a more efficient microenvironment allowing for cell interactions via secreted factors in mono‐ and cocultures and could be applied for many other tissues.